Health and Economic Consequences of Counterfeit Drugs - Seiter, A. (2012)
"Counterfeit Drugs Kill" is the slogan the World Health Organization (WHO) uses in its anti-counterfeiting campaign. International organizations, governments of developed and developing countries, and the pharmaceutical industry created the IMPACT initiative (International Medical Products Anti-Counterfeiting Taskforce) to take on the thriving illegal industry that makes profits by selling fake drugs. However, before committing resources, policy makers want to assess the burden caused by counterfeit drugs in comparison with other health problems that compete for the limited resources available.